TINDAKAN PENCEGAHAN KARIES GIGI PADA SISWA SEKOLAH DASAR BERDASARKAN TEORI HEALTH BELIEF MODEL - Lidia Septianingtias Setiari; Muji Sulistyowati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2017)
Dental caries is one of the serious health problem in school age children. The maintenance of dental and oral health need to be done early in the prevention of dental caries. This study was conducted to analyze  the application of Health Belief Model theory on dental caries prevention  in elementary school students. This research was quantitative study with a cross-sectional approach. Sample were fifth grade student at SDN Kedurus 1 Surabaya amount to 53 students and taken by simple random sampling. The independent variable were perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy and cues to action. The dependent variable of this study was action in the prevention of dental caries. Quantitative data was analyzed using Spearman correlation test and logistic regression. The respondent action to prevent dental caries was good. There was a correlation between perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy and cues to action with action in preventing dental caries. This research concluded that perceived susceptibility was the most influencing factor in preventing dental caries. It was suggested to increase the effort of  promotive and preventive in school so that the students can more diligent in doing dental caries prevention action. Keyword: health belief model, dental caries, behavior of students